Does body satisfaction influence self-esteem in adolescents' daily lives? An experience sampling study. (December 2015) - Fuller-Tyszkiewicz, Matthew; McCabe, Marita; Skouteris, Helen; Richardson, Ben; Nihill, Kristy; Watson, Brittany; Solomon, Daniel
Abstract: This study examined, within the context of the Contingencies of Self-Worth model, state-based associations between self-esteem and body satisfaction using the experience sampling method. One hundred and forty-four adolescent girls (mean age = 14.28 years) completed up to 6 assessments per day for one week using Palm Digital Assistants, in addition to baseline measures of trait body satisfaction and self-esteem. Results showed considerable variation in both state-based constructs within days, and evidence of effects of body satisfaction on self-esteem, but not vice versa. Although these state-based associations were small in size and weakened as the time lag between assessments increased for the sample as a whole, individual differences in the magnitude of these effects were observed and predicted by trait self-esteem and body satisfaction. Collectively, these findings offer support for key tenets of the Contingencies of Self-Worth model.